Weighted differentiation composition operators on the $Q_K(p,q)$ spaces and‎ their essential ‎norms‎ - Mostafa Hassanlou; Ebrahim Abbasi; Ali Ebrahimi (Journal of Mahani Mathematical Research)
In this paper, firstly we obtain characterization for boundedness of the weighted differentiation composition operator  from $Q_K(p,q) $ space into weighted Zygmund space. Then we give an estimation for the essential norm of such an operator on the mentioned spaces.  As an application, we present a characterization for the compactness of the above operator.